PENGALIHAN HAK RUMAH NEGARA KEPADA PEGAWAI NEGERI DALAM PENERAPAN HUKUM SEWA BELI - Nia Kurniati (Faculty of Law Universitas Padjadjaran, 2018)
ABSTRAKPengadaan Rumah Negara bagi pegawai negeri berfungsi sebagai tempat tinggal atau hunian dan sarana pembinaan keluarga serta menunjang pelaksanaan tugas Pejabat dan/atau Pegawai Negeri. Terdapat penggolongan status rumah-rumah negara, diantaranya terdapat rumah negara yang dapat dialihkan haknya kepada pegawai negeri. Dalam pengalihan hak atas rumah negara kepada pegawai negeri harus dijamin pula keberlangsungan haknya atas tanah. Metode penelitian dalam penelitian ini adalah penelitian yuridis normatif, didasarkan pada data sekunder berupa bahan hukum primer dan bahan hukum sekunder terkait rumah negara. Analisis data menggunakan metode analisis yuridis kualitatif. Hasil penelitian, (i) Perjanjian sewa beli merupakan alas hak pengalihan rumah negara golongan III kepada pegawai negeri; (ii) Pengalihan hak rumah negara ditandai dengan penerbitan surat tanda bukti hak milik atas rumah negara oleh pejabat yang berwenang dan pelepasan hak atas tanahnya oleh Dirjen Cipta Karya Departemen Pekerjaan Umum sebagai dasar penerbitan Sertifikat Tanah oleh Kantor Pertanahan.Kata kunci: pengalihan hak; pegawai negeri; rumah negara; sewa beli. ABSTRACTProcurement of State Housing for civil servant functions as a means of residency or housing and medium for family development as well as to support the duty of officers and/or civil servants. There exists a classification of state housing status, among which are state housing whose rights can be transferred to civil servants. In the event of a transfer of state housing rights to civil servants, the sustainability of their rights over the land must also be guaranteed. The research method used in this study is normative juridical research, based on secondary data in the form of primary law materials and secondary law materials related to state housing. Data analysis is performed using qualitative juridical analysis method. Results of the study, (I) Rent-buy agreement is the base of group III state housing transfer rights to civil servants; (ii) Transfer of state housing rights is indicated by the publication of the letter of evidence of ownership rights over the state housing by authorized officer and the release of its land rights by Dirjen Cipta Karya Departemen Pekerjaan Umum (Director General of Creation and Works of the Ministry of Public Works) to serve as the base for the publication of its Land Certificate by the Land Office.Keywords: rent-buy; state housing; state’s house; transfer of rights.